Tontonan Edukasi Berbasis Islami untuk Penguatan Karakter Santri MDTA Nurul Iman III: Islamic-Based Educational Movie to Strengthen Students’ Character at MDTA Nurul Iman III - Kumalasari, Cyintia; Muttaqin, Muhammad Zaenal; Zaini, Abdul Kudus (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Character education is the foundation for instilling good morality in children. Unfortunately, the rapid development of information technology today still cannot match the role of parents as the first teacher to educate children. In this case, the role of the family, especially parents, is very important as role models or role models that children can emulate in their environment, both at school and at home. Elementary school-age students generally like animated films or cartoons. However, not all animated films or cartoons can teach good values and strengthen character to elementary school students. The animated film Nussa and Rara was chosen because this animated film provides many examples of manners and manners towards parents and teachers as well as manners in getting along with friends. Worship education is also demonstrated without being frontal or forced to instill an understanding of the importance of worship from an early age. Watching the animated film “Nussa: The Movie” has been proven to help influence good values as character strengthening for students, especially to filter the flow of technology and information.